Barriers to Help-Seeking Behavior towards Counseling in Chinese Students - Gunawan Gunawan; Dwi Yuwono Puji Sugiharto; Sugiyo Sugiyo; Sunawan Sunawan (International Conference on Science, Education, and Technology, 2023)
Counseling help-seeking behavior as an effort to solve personal-social problems is influenced by the cultural values ​​of an ethnic group. The purpose of this study was to analyze the barriers to help-seeking behavior in school counseling services for students of Arab, Chinese and Javanese ethnicity in Surakarta. The research method is quasi-qualitative with an ethnographic approach. The instruments used were virtual and in-depth interview guidelines. The research source used 15 Thionghoa participants. Retrieval of data with in-depth interview techniques. Data were analyzed using Qualitative Data Analysis with the NVivo12 application. There are four main themes as a result of data analysis. The results showed that the Chinese ethnicity was influenced by a culture of collectivity and independence. The implication of this research is that in order to improve counseling help-seeking behavior, a counselor needs to understand the cultural values ​​of each learner.